2011
DOI: 10.1002/ejoc.201100997
|View full text |Cite
|
Sign up to set email alerts
|

Inductive and Mesomeric Effects of the [60]Fulleropyrrolidine Fragment and [60]Fullerene Sphere: A Quantitative Evaluation Based on Theory and Experiments

Abstract: Inductive and mesomeric effects of the [60]fulleropyrrolidine (Pyr=C(60)) and the [60]fullerene (C(60)) molecular frameworks have been investigated by linear free energy relationship analyses. The electronic effects of these moieties have been studied by expressly designing [60] fulleropyrrolidine derivative 1, which has a C-H bond alpha to both a carbonyl group (CH(alpha)) and a C(60) cage. The extent of polarization of such a bond was then used to probe electron-withdrawing perturbation induced by the fuller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Nevertheless, a rationalization of the p K a values of a series of related compounds can be successfully attempted in terms of factors, such as bond polarization and/or relative stability of the protonated and deprotonated species. Both factors can be conveniently expressed by molecular descriptors, attainable at different levels of theory, which, in turn, can be used in a linear free energy relationship (LFER) analysis to estimate p K a values. ,, These descriptors have been previously calculated at both low level of theory (empirical, AM1, HF/STO-3G, HF/3-21G, HF/3-21G(d)) ,,,− ,, and Hartree–Fock (HF) or DFT methods with larger basis sets. Although, as a general rule, the highest possible computational methods have to be adopted, there are several examples where the use of HF or DFT methods with larger basis sets does not necessarily lead to significant improvements in correlations with the experimental data. ,, It has also been demonstrated that the atomic charge densities on the α-hydrogens, δ(H α ), can be used to monitor even small variations of acidity as a function of conformational and/or configurational changes, when these changes influence the degree of polarization of the bonds involved in the dissociation process. ,,, Thus δ(H α ) values have been calculated and used to predict the p K a of the investigated ketones as previously reported. , As a first step, we have determined the most representative conformers of the keto form of the experimentally investigated 2-nitrocycloalkanones both at the semiempirical AM1 and B3LYP/6-31G(d,p) levels of theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a rationalization of the p K a values of a series of related compounds can be successfully attempted in terms of factors, such as bond polarization and/or relative stability of the protonated and deprotonated species. Both factors can be conveniently expressed by molecular descriptors, attainable at different levels of theory, which, in turn, can be used in a linear free energy relationship (LFER) analysis to estimate p K a values. ,, These descriptors have been previously calculated at both low level of theory (empirical, AM1, HF/STO-3G, HF/3-21G, HF/3-21G(d)) ,,,− ,, and Hartree–Fock (HF) or DFT methods with larger basis sets. Although, as a general rule, the highest possible computational methods have to be adopted, there are several examples where the use of HF or DFT methods with larger basis sets does not necessarily lead to significant improvements in correlations with the experimental data. ,, It has also been demonstrated that the atomic charge densities on the α-hydrogens, δ(H α ), can be used to monitor even small variations of acidity as a function of conformational and/or configurational changes, when these changes influence the degree of polarization of the bonds involved in the dissociation process. ,,, Thus δ(H α ) values have been calculated and used to predict the p K a of the investigated ketones as previously reported. , As a first step, we have determined the most representative conformers of the keto form of the experimentally investigated 2-nitrocycloalkanones both at the semiempirical AM1 and B3LYP/6-31G(d,p) levels of theory.…”
Section: Resultsmentioning
confidence: 99%
“…Although, as a general rule, the highest possible computational methods have to be adopted, there are several examples where the use of HF or DFT methods with larger basis sets does not necessarily lead to significant improvements in correlations with the experimental data. [26][27][28][29]44,46 It has also been demonstrated that the atomic charge densities on the α-hydrogens, δ(H α ), can be used to monitor even small variations of acidity as a function of conformational and/or configurational changes, when these changes influence the degree of polarization of the bonds involved in the dissociation process. 15,16,22,23 Thus δ(H α ) values have been calculated and used to predict the pK a of the investigated ketones as previously reported.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…M.p. 303-304 8C; 1 H NMR (300 MHz, CDCl 3 ): d = 9.05 (d, 3 JA C H T U N G T R E N N U N G (H,H) = 9.66 Hz, 3 H), 8.74 (br s, 3 H), 8.13 (d, 3 27 (11), 575 (17), 449 (28), 189 (29); UV (c = 1.77 10 À5 in CHCl 3 ): l max (e) = 244 (31 192), 287 (23 932), 347 (13 672).…”
Section: Methodsmentioning
confidence: 99%
“…Attention was preliminarily focused on the atomic charges located on phosphorus (d P ) and oxygen (d O ) atoms of the P=O group, as well as on the length of the P=O bond d P=O (Table S1 of Supporting Information). The choice of the first two descriptors was suggested by the knowledge that charges localized on acidic hydrogen atoms or on atoms carrying acidic hydrogen atoms, assessed by quantum mechanical calculations at either semi-empirical [11][12][13][14][15][16][17][18][19] or ab initio level, [11,[20][21][22][23][24][25][26] are effective descriptors of acidity that can sensitively reflect even small conformational [16,17] and configurational [16][17][18]20] changes in the structure of the substrate. Interestingly, several examples [11,[22][23][24][25][26] showed that improvements in the level of theory of the quantum mechanical methods used to assess the molecular descriptors (e.g., HF or DFT instead of semiempirical methods, as well as larger basis sets within HF or DFT approaches) do not necessarily lead to significant improve- ment in the quality of the linear free-energy relationship (LFER) correlations.…”
Section: Theoretical Investigation Of Electronic Property-configurati...mentioning
confidence: 99%
See 1 more Smart Citation